1997
DOI: 10.1042/cs0930235
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin-Induced Attenuation of Noradrenaline-Mediated Vasoconstriction in Insulin-Resistant Obese Zucker Rats

Abstract: 1. Insulin resistance is associated with hypertension but the underlying mechanism is unclear. We tested the hypothesis that insulin-induced vasodilatation is impaired in insulin-resistant obese Zucker rats. We studied mesenteric artery (approximately 220 microns diameter) function before the development of hypertension in 3-month old obese Zucker rats and age-matched lean rats. 2. In vessels from lean rats, insulin at concentrations of 50, 500 and 5000 m-units/l attenuated the constriction in response to nora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…31 In support of this hypothesis, several studies have suggested that insulin resistance and hyperinsulinemia play a pathogenic role in the development of high blood pressure hypertension. 32 This suggestion is supported by the observation that drugs that specifically counter insulin resistance (and attenuate hyperinsulinemia) also exhibit antihypertensive effects.…”
Section: Midaoui and De Champlainmentioning
confidence: 89%
“…31 In support of this hypothesis, several studies have suggested that insulin resistance and hyperinsulinemia play a pathogenic role in the development of high blood pressure hypertension. 32 This suggestion is supported by the observation that drugs that specifically counter insulin resistance (and attenuate hyperinsulinemia) also exhibit antihypertensive effects.…”
Section: Midaoui and De Champlainmentioning
confidence: 89%
“…Endothelium-dependent vasorelaxation has been reported to be impaired in several models of obesity, including Zucker obese rats 31,32 and in vessels from rats with diet-induced obesity. 13,29 Interestingly, Auguet et al 33 found that the contractile response to PE of isolated aortic segments of Zucker obese rats was reduced only when the endothelium was denuded, and that this effect was no longer persistent in the intact vessel.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effect of insulin on NO production, we compared the cumulative dose response to PE (1 nmol/l to 10 mol/l) before and after a 2-h incubation with insulin (100 mU/ml Actrapid; Novo Nordisk) (22,23). This dose of insulin was found to be optimal in preliminary experiments.…”
Section: Methodsmentioning
confidence: 99%